Tailoring Scripture with Citation Formulae: Clues about Early Christian Views of the Holy Books and the Holy God - Gabrielson, Timothy A. (Lexington Books/Fortress Academic, 2024)
Phrases like "scripture says" appear unremarkable, but citation formulae provide clues about matters as diverse as the media consciousness of the evangelists, emerging trinitarianism in Hebrews, and Paul's theology of scripture. Tailoring Scripture with Citation Formulae includes an analysis and catalogue of early Christian formulae.